Rattus nitidus Hodgson 1845 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus nitidus Hodgson 1845 Rattus nitidus Hodgson 1845, Ann. Mag. Nat. Hist., ser. 1, 15: 267. Type Locality: Nepal. Vernacular Names: White-footed Indochinese Rat. Synonyms: Rattus aequicaudalus (Hodgson 1849); Rattus guhai (Nath 1952); Rattus horeites (Hodgson 1845); Rattus manuselae Thomas 1920; Rattus obsoletus Hinton 1919; Rattus rahengis Kloss 1919; Rattus ruber (Jentink 1880); Rattus rubricosa (Anderson 1879); Rattus subditivus Miller and Hollister 1921; Rattus vanheurni Sody 1933. Distribution: Mainland Southeast Asia from S China (SE Xixang, Yunnan, Sichuan, Guizhou, Hunna, Guangxi, Guangdong, Fujian, Jiangxi, Zhejiang, Shanghai, Jiangsu, Anhui, S Shaanxi, SE Gansu, and Hainan Isl; Wang, 2003), Vietnam (including the coastal islands of Cat Ba and Thô Chu; Kuznetsov, 2000), Laos, N Thailand, Burma, Bangladesh, Nepal, Bhutan, and N India (Uttar Pradesh, Sikkim, West Bengal, Arunachal Pradesh, Meghalaya, Tripura, Mizoram, and Manipur; Agrawal, 2000); this distribution probably represents the indigenous range (Musser and Holden, 1991). Records east of the continental shelf are from C Sulawesi, Luzon Isl in the Philippines (recorded only from Benguet Province, Heaney et al., 1998; Musser, 1977 a Musser and Holden, 1991), Pulau Seram in the Moluccas, the Vogelkop Peninsula of the Prov. of Papua (= Irian Jaya), and the Palau Isls (east of the Philippines; Barbehenn, 1974); this distribution likely represents introductions mediated by human agency (Musser and Holden, 1991). Conservation: IUCN – Lower Risk (lc). Discussion: Rattus norvegicus species group. Association of synonyms documented by Corbet and Hill (1992), Ellerman (1941), Khajuria et al. (1977), J. T. Marshall, Jr. (1977 a , b ), Musser (1981 c ), Musser and Holden (1991), and Taylor et al. (1982). Phallic morphology described by Yang and Fang (1988) in context of assessing phylogenetic relationships among Chinese murines. Yang et al. (1994) and Zeng et al. (1996 a , b , 1999) reported various aspects of population ecology for Chinese populations, ...